Integrating Islamic Values Into English Instruction For Junior High School Students Aligned With The Independent Curriculum - Ersyadila, Ghina Fidaraini; Rahmi, Rika; Hasibuan, Kalayo (Lembaga Riset dan Inovasi Almatani, 2025)
This research aims to integrate Islamic values in teaching English for junior high school students based on Merdeka Curriculum. Using a qualitative approach, this study collected data through sources on journal articles and analysis of curriculum documents and relevant teaching materials. Islamic values, such as honesty, discipline, and mutual respect, were identified and analyzed to find out how they are applied in the context of English learning. The results show that the integration of these values can not only improve students' understanding of the language, but also shape positive characters that are in line with Islamic teachings. In addition, teaching strategies involving collaborative activities and self-reflection proved effective in facilitating the application of these values. This study recommends the development of more contextualized and relevant teaching materials, as well as training for teachers to understand and implement this approach effectively. Thus, the results of this study are expected to contribute to the development of education that is not only oriented towards language skills, but also the formation of student character in accordance with Islamic values within the framework of the Merdeka Curriculum.